Impacts of hydraulic retention time on granule behaviour and reactor activity during hydrocarbon degradation in aerobic granular reactors (AGRs) with phytotoxicity analysis. (July 2020) - Ghosh, Sayanti; Chakraborty, Saswati
Abstract: The paper is about impacts of hydraulic retention time (HRT) on granule characteristics, reactor activity, hydrocarbon removal efficiency and removal mechanism while treating emulsified diesel wastewater in aerobic granular reactors (AGRs). AGR with shortest HRT (12 h) achieved maximum 4.72 ± 0.05 mm granule size and extracellular polymeric substances (EPS) of 400.31 ± 0.01 mg/g volatile suspended solids (VSS) with 68.85 ± 0.06% of hydrocarbon removal. Short HRT (12 h) provided maximum biomass concentration (6.38 ± 0.05 g/L) to achieve maximum biomass activity of 8.33 ± 0.21 mg COD/mg VSS.day among the AGRs. But longest HRT (48 h) played major role providing longer reaction time for 90.31 ± 0.26% hydrocarbon removal. Degradation of short and long chain alkanes (C6 –C7, C9 –C10, C11 –C13, C15 –C18, C27 ) were observed in the AGRs which further produced fatty acids as metabolites. In steady state COD removal rate varied between 71- 90% which was completely depended on HRT values and hydrocarbon removal efficiency of the reactors. Nitrogen balance suggested that maximum nitrogen was utilized in biomass growth and about 2–20% nitrification occurred in the AGRs. About 24–48 h HRT with 0.125–0.25 kg/m 3 .day hydrocarbon loadings providing below 77 mg/L effluent hydrocarbon was recommended for successful AGR treatment to avoid phytotoxicity after disposal. Graphical abstract: Image 1 Highlights: Bigger granules in 12 h HRT and 90% oil removal in 48 h HRT. Hydrocarbons converted into fatty acids and undergone β-oxidation. About 2–20% nitrogen in complete nitrification and rest in biomass growth. High biomass concentration in 12 h HRT provided maximum reactor activity. Effluent of 48 h HRT provided maximum germination and chlorophyll in plants.